Prevalence of low back pain in Iranian nurses: a systematic review and meta-analysis - Yosra Azizpour; Ali Delpisheh; Zahra Montazeri; Kourosh Sayehmiri (BMC, 2017)
Abstract Background Low back pain (LBP) as a musculoskeletal disorder is one of the most common occupational injuries in nurses but there isn't any valid measure of the prevalence of LBP in Iranian nursing. In order to increase the power and improve the estimates of the prevalence of LBP in Iranian nurses, a comprehensive meta-analysis was carried out. A summary measure of all studies conducted in this field was found and distributions of LBP were evaluated based on different variables. Methods Inclusion criteria included articles with prevalence of LBP in Iranian nurses, who had at least six months of work experience without any trauma, injuries to spine, or any underlying disease. The keywords"prevalence, low back pain, nurses", and "Iran" were used as part of this search. Databases such as Pubmed, Web of Science, Science direct, Scopus, IranMedex, Irandoc, Magiran, SID, CIVILICA, IMEMR and Google scholar were searched up to and including 15 June 2016. For data extraction a form was designed that included the following variables: Author names, province, sample size, age, gender, marital status, work experience, body mass index, job type, smoking status, work schedule, year of publication, type of standard questionnaire, prevalence of LBP, studies' quality score and climate classifications. Data analysis was carried out using fixed and random effects model. Heterogeneity between studies was assessed by using the I 2 and Q tests. Results In all 1250 articles were identified and 22 articles with 9347 participants met the inclusion criteria for meta-analyses after filtering. The prevalence of low back pain during their working life and during the last year, was estimated at 63% (95% Confidence Interval (CI): 57.4-68.5) and 61.2% (95% CI: 55.7-66.7) respectively. The prevalence rate of this disorder was 58.7% (95% CI: 35.8-81.7) and 60.4% (95% CI: 52.2-68.6) among men and women respectively. Furthermore, prevalence's of LBP were 59.5% in wards nurses, 50.3% in operating room technicians, and 39.4% in aid nurses. Conclusions The results showed the high prevalence of LBP injury in nurses, especially female nurses. The effect of musculoskeletal disorders such as LBP may be reduced by considering proper observation of the principles of ergonomics in the workplace, performing physical examinations on a regular basis, identifying risk factors in the advancement of musculoskeletal disorders and then trying to fix them.